Perilaku Agresif Siswa SMP: Studi Kasus Pada 2 Siswa Kelas VIII SMP Negeri 3 Pengadegan Purbalingga - Ashidiq, Khabib (Yinyang: Jurnal Studi Islam Gender dan Anak, 2019)
This study is based on the phenomena that occur in the field that show symptoms of aggressive behavior in class VIII Pengadegan Middle School 3. Students who behave aggressively are students who understand the problem personally. This type of research is case study research and is used to reveal individual data. The subjects studied were 2 students taken from students who behaved aggressively with different causative factors for each individual. Data collection methods used are interview, observation, and documentation methods. While the data analysis uses technical interactive analysis of miles and huberman models. Aggressive behavior is a response to frustration, anger, fear by trying to hurt others. The forms of aggressive behavior carried out by the individual in responding to frustration, anger, fear, among others, attacking the physical, attacking an object, verbally or symbolically threatening and aggravating other people and demanding attitudes, violations of property rights or attacking other areas. The results showed that the two individuals who behaved aggressively both verbally and non-verbally were caused by several different backgrounds as well as factors that influenced both internally and externally.